Critical Thinking and Challenges for Education for Democratic Citizenship: an ethnographic study in primary schools in Greece - Ioanna Noula (Universidade Federal do Rio Grande do Sul, 2018)
This paper reports on an ethnographic multiple case study in Greece. It explores teachers' practices regarding the education of critically thinking citizens ten years into the implementation of an integrated curriculum reform. By means of classroom observations and semi-structured interviews this research explored the role of critical thinking in the classrooms. Findings suggest that teachers refrain from practices that advance critical thinking skills and pupils' empowerment. Instead they tend to implement traditional practices, while their work is largely determined by the standards of achievement set by University Entrance Exams and parents' aspirations. The paper concludes that prevailing expectations in the Greek primary school interfere with the development of pedagogical relationships that would promote critical thinking obstructing the attainment of the aims of the integrated curriculum reform and compromising the project for democratic citizenship.